The challenges of E-learning system: Higher educational institutions perspective - Leila Shahmoradi; Vahid Changizi; Esmaeil Mehraeen; Azadeh Bashiri; Behrooz Jannat; Mahsa Hosseini (Wolters Kluwer Medknow Publications, 2018)
INTRODUCTION: The development of information technology (IT) in education has led to the expansion of new teaching and learning methods at universities. Implementation of E-learning programs at Iran's universities as well as assessing the prerequisites and level of preparation of learners to attend E-learning environments require extensive study. Therefore, this study examined to investigate the challenges of E-learning system at Tehran University of Medical Sciences. METHODOLOGY: This study was a descriptive and cross-sectional one that conducted in 2016_2017. The statistical populations were all of the students that have an E-learning course in Tehran University of Medical Sciences, from whom, 300 were selected to participate in the study using a stratified random sampling method. The tool of the study was a researcher-made questionnaire. The data were analyzed through SPSS software. RESULTS: According to the findings of this study, about half of the participants (40%) had problems accessing the technology, and only 26.4% of the participants had good preparation for the use of E-learning system. Furthermore, a significant difference was found between the challenges of skill and culture of the participants (P value = 0.01). CONCLUSION: Success in the implementation of E-learning educational system as one of the main approaches in managing knowledge and educational needs of higher education organization will not be achieved without identifying the different skill, technical and cultural challenges. To overcome this challenge, establishing IT infrastructure and standards, using experiences of the leading countries in the field of E-learning, creating proper culture, and familiarizing learners and teachers to the development and use of E-learning materials are necessary.